Postmodernism and Climate Issues: Deconstruction of Media Narratives and Environmental Communication Actions in Contemporary Urban Society - Razali, Geofakta; Winarty, Shenthya; Bakti Abdillah Putra (Indonesian Scientific Publication, 2023)
This study explores the impact of postmodernism on media narratives in climate issues, especially within the scope of communication in today's urban environments. Through a qualitative approach, this study deconstructs various media narratives on climate issues to understand their influence on the views and communicative actions of urban society. The analysis samples from various media platforms, including online news, social media, and digital publications, focusing on the years 2022-2023 to ensure data currency. The theoretical framework in this study integrates postmodernism concepts with communication theories, providing insights into the formation and reception of climate narratives by the audience. The findings indicate a shift in the way media narrates climate issues, moving from traditional narratives towards more fragmented and diverse ones, in line with postmodernism characteristics. This understanding is crucial for developing effective climate communication strategies that encourage active participation and concrete actions from city dwellers. Thereby, this study significantly contributes to climate communication research, highlighting the influence of media narratives on society's views and actions in facing climate issues within a complex and heterogeneous socio-cultural context.